PHEOCHROMOCYTOMA PRESENTING AS ACUTE CORONARY SYNDROME IN AN ELDERLY PATIENT: A CASE REPORT FROM THONG NHAT HOSPITAL - Phúc, Nguyễn Ngô Gia; Thành Vĩ, Lâm; Văn Quảng, Lý; Tấn Hùng, Huỳnh; Kỳ Văn, Hạ; Đỗ Huy Hoàng, Nguyễn; Võ Công Nguyên, Đỗ; Thị Mai Hương, Nguyễn; Thanh Huân, Nguyễn (Journal of Health and Aging, 2025)
Pheochromocytoma is a rare endocrine cause of secondary hypertension. The definitive diagnosis requires a combination of biochemical testing and imaging studies. Management of pheochromocytoma-induced hypertension involves appropriate pharmacologic therapy followed by surgical resection of the adrenal tumor. In this report, we present the case of an elderly patient who was admitted with chest pain and initially diagnosed with acute coronary syndrome. However, invasive coronary angiography revealed no significant stenosis. Subsequent investigations confirmed the diagnosis of pheochromocytoma. The patient underwent successful medical stabilization and surgical removal of the tumor. This case highlights the importance of multidisciplinary collaboration in the diagnosis and treatment of pheochromocytoma at Thong Nhat Hospital.